Health priorities and treatment preferences of adults with epilepsy: A narrative literature review with a systematic search - Hill, Chloé E.; Vanderboll, Kathryn; Parent, Jack M.; Skolarus, Lesli E.; Zahuranec, Darin B. (Epilepsy & behavior, 2025)
•Seizure frequency is just one of several seizure-related patient priorities.•Health priorities include a range of cognitive, psychological, and physical factors.•Support needs and life goals are important to consider in treatment plans.•An individual’s priorities and goals must be explicitly queried, not assumed, to provide patient-centric care. The care of people with epilepsy can be complex. Seizure control is a top priority, however there are other important health-related factors that can impact the well-being of a person with epilepsy. Understanding the range of health priorities and treatment preferences is a critical step in facilitating patient-centered care. In this narrative review, we queried four electronic databases with search terms including patient preferences, needs, priorities, and goals. In total, 20 articles met criteria to be included in the review; these included both quantitative and qualitative analyses of patient responses. Key issues identified were a variety of seizure-specific priorities (such as frequency, duration, severity, warning) and non-seizure medical priorities (such as cognition, mood, physical side effects). Support needs (such as psychological support, improved access to health care) and life goals (such as driving, relationships, work) were also prevalent and emphasized. The range of these findings support the importance of querying individual priorities to promote patient-centered care. Additionally, our results demonstrate that non-medical considerations are an important piece of the illness of epilepsy and should be considered in health care encounters as possible to improve patient outcomes and overall well-being.